Pancreatic response of spontaneously hypertensive rats to the exogenous administration of melatonin in the spring and autumn - R. Yanko; V. Berezovsky; M. Levashov; L. Plotnikova; O. Chaka (Regulatory Mechanisms in Biosystems, 2016)
The aim of the study was to investigate and compare the effect of exogenous melatonin administration on the morphofunctional state of the exocrine and endocrine parts of the pancreases of spontaneously-hypertensive rats (SHR line) in spring and autumn. The research was conducted on 48 male SHR line rats, age 4 months. The rats of the experimental group received melatonin (Unipharm Inc.,USA) every day (at 10 am) orally at a dose of 5 mg/kg of body weight. The duration of the experiment was 28 days. Morphofunctional activity of the exocrine and endocrine parts of the pancreas was assessed using morphological and morphometric methods. The histological preparations were made by the standard methods. The slides were photographed using a digital camera on a Nikon microscope. The morphometric analysis was performed on digital images using the computer program Image J. The morphological signs of the exocrine pancreas activity were greater in the control rats in spring compared to autumn. Conversely, the activity of the endocrine part of the pancreas in control animals was higher in autumn, than in spring. Exocrine pancreas activity increases after administration of melatonin regardless of time of the year. This was evidenced by the increase in size and height of the epithelial acini, and the number of exocrinocytes placed in them. The width of the interlobular and interacinus connective tissue layers in the pancreas decreased in spring (mostly) and in autumn. The activity of the endocrine part of the pancreas increased after administration of melatonin in spring. Proof of this was an increase in the number and size of islets of Langerhans and the number of endocrinocytes they contained, compared with control values. The number and size of islets of Langerhans, the number and density of the endocrinocytes they contained decreased in the rats which received melatonin in autumn. This indicates a reduction of the endocrine pancreas activity. These results may have implications for therapeutic dosing of melatonin in patients with hypertension in different seasons of the year.